Artemísia absinthium minimiza a toxicidade induzida por paracetamol em camundongos - Franco, Fernando Wendel (2015)
Acetaminophen is a popular analgesic associated with toxic ingestions. There are many studies about prevention of APAP induced hepatotoxicity including the medicinal plants. Artemisia absinthium (AA) is one of them, but its extract against the hepatotoxicity induced by APAP were not yet investigated. This study aimed to investigate the antioxidant effects of AA's aqueous extract against the APAP's intoxication in mice. Our results show that AA present high poliphenol's concentrations and flavonoids. In vitro tests, AA decreased the basal and pro-oxidants induced lipid peroxidation in mice homogenated tissues (10 to 25μg). Also, DPPH radical's (2,2-diphenyl-1-picrylhydrazyl) scavenger activity was reduced (100μg) (p≤0.05). Ex vivo, AA reduced the lipid peroxidation, induced by iron reduced, in mice liver (from 10 to 100μg) and kidneys (at 100μg) (p≤0.05). The intoxication with APAP determined a significant increase in lipid peroxidation and also a decrease in non-protein thiol levels and of the enzymes superoxide dismutase e catalase activities (p≤0.05). Moreover, the APAP depicted an increase of the transaminase enzymes activities in serum, and also decreased the cell viability in liver and brain's mice (p≤0.05). Our results show that the aqueous extract of AA had hepatoprotective properties against toxicity induced by APAP. In general, the hepatoprotective effects of AA against an intoxication with APAP were related to its antioxidant potential in vitro and ex vivo. Finally, further studies are needed to highlight the mechanism of AA aqueous extract action, especially its effects in the mitochondrial dysfunction prevention.